Incidence of cardiovascular disease and mortality in underweight individuals. Issue 2 (22nd February 2021) - Kwon, Hyuktae; Yun, Jae Moon; Park, Jin Ho; Cho, Be Long; Han, Kyungdo; Joh, Hee‐Kyung; Son, Ki Young; Cho, Su Hwan
Abstract: Background: Few studies have evaluated the association between being underweight and having cardiovascular disease in the general population. We investigated the incidence of stroke, myocardial infarction (MI), and all‐cause mortality according to detailed underweight categories in a large population cohort. Methods: We included 4 164 364 individuals who underwent a health examination that was conducted as part of the Korean National Health Insurance Service between January 2009 and December 2012 and followed them up to determine the incidence of stroke, MI, and all‐cause mortality until 31 December 2016. Based on the body mass index, the study population was categorized into normal (18.50–22.99), mild (17.00–18.49), moderate (16.00–16.99), and severe underweight (<16.00) groups. Cox proportional hazards analyses were performed to calculate the hazard ratio for stroke, MI, and mortality according to the severity of underweight in reference to the normal weight. We adjusted for age, sex, lifestyle, economic status, co‐morbidity, blood pressure, glucose, lipid level, and waist circumference. Results: The mean age of the 4 164 364 eligible subjects in this study cohort was 44.4 ± 14.3 years, and 46.1% of the participants were male; 46 728 strokes, 30 074 MIs, and 121 080 deaths occurred during 27 449 902 person‐years. The incidence of stroke, MI, and all‐cause mortality increased proportionally with the severity of underweight in the multivariate model. This proportional association became more evident when the waist circumference was additionally adjusted. The respective hazard ratios (95% confidence intervals) for mild, moderate, and severe underweight were 1.10 (1.06–1.15), 1.11 (1.02–1.20), and 1.38 (1.24–1.53) for stroke; 1.19 (1.14–1.25), 1.40 (1.27–1.53), and 1.86 (1.64–2.11) for MI; and 1.63 (1.60–1.67), 2.10 (2.02–2.17), and 2.98 (2.85–3.11) for all‐cause mortality. In stratified analyses based on waist circumference, the severity of underweight was consistently associated with a higher risk of stroke, MI, and death. Conclusions: The severity of underweight was associated with a higher risk of stroke, MI, and all‐cause mortality.